Electricity access and social sustainability in Mozambique - Salite, Daniela; Cotton, Matthew; Kirshner, Joshua (Oxford Policy Management, 2020)
The demand for access to electricity in developing countries is rapidly increasing as intergovernmental organisations, national governments, and business leaders recognise the social and economic value of infrastructure investment. The institutions that govern energy investment and planning recognise a ‘trilemma’ of system development: low-carbon energy sources are needed to meet global climate change mitigation goals, while also meeting service reliability demands and energy security measures alongside maintaining service affordability, particularly for residents on the lowest incomes in rural, urban, and peri-urban communities. Integrating traditional, centralised grid networks based upon large-scale generation technologies (in the case of Mozambique, this includes hydropower from the Cahora Bassa Dam) with decentralised off-grid renewables such as solar projects in rural communities is a significant technical and governance challenge. Energy providers are tasked with a social mandate to deliver good quality electricity at an affordable price to consumers while widening access to underserved populations. Providing access to clean and reliable energy sources is embodied in Sustainable Development Goal 7 as one of the preconditions for socioeconomic development, poverty reduction, and human wellbeing (Pueyo and Maestre, 2019; UN Energy, 2005). International development practitioners and policy networks recognise the tangible benefits of electricity as a form of energy service provision. These tangible benefits include lighting and powering appliances at domestic, private, and institutional levels and increased telecommunications coverage, which collectively provide new personal and business development opportunities, healthcare and food safety benefits, and improved leisure and night-time education prospects (UN Energy, 2005). They also minimise the health risks and ecological impacts associated with black-carbon fuels such as charcoal, which diminish air quality within residential buildings (Anenberg, 2017) and lead to deforestation (Sedano et al., 2016). In order to enhance electricity sector performance, many sub-Saharan African countries have implemented significant governance reforms. It is necessary, however, to evaluate whether such reforms facilitate expanded social access to electricity, whether they improve service quality, public utility, and financial stability, and whether they lead to broader social and environmental sustainability goals. In this policy brief, we assess these dimensions related to the case of Mozambique, a country where major progress has been made to increase population-wide access to electricity from around 6% in 2004 (Chambal, 2010) to 32% in 2019 (EDM, 2020a). Though policy progress is significant, challenges remain, particularly in rural areas, where only around 6% of the population have electricity access (EDM, 2018a).
Keywords: G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; ⛔ No DOI found

Humanitarian Response Plan Mozambique (Humanitarian Programme Cycle 2021, 2020)
OCHA Humanitarian Response Plan for Northern Mozambique Conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; displaced communities / comunidades deslocadas

Relatório Independente da Iniciativa de Transparência na Indústria Extractiva - EITI (Extractive Industries Transparency Initiative (EITI), 2020)
Este é o nono relatório de reconciliação dos pagamentos efectuados pelas empresas que operam na indústria extractiva e os recebimentos do Estado. Foram reconciliadas 97% das receitas tributárias provenientes da indústria extractiva. As diferenças apuradas entre os pagamentos das empresas e os recebimentos do Estado correspondem a 0,17% dos montantes confirmados pelo Estado em 2019.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Instituições que aprendem - Relatório para a XXVII Cimeira Ibero-Americana de Chefes de Estado e de Governo - Oliván Cortés, Raúl (XXVII Cimeira Ibero-Americana, 2020)
A pandemia da Covid-19 surgiu de súbito num momento de transição para as instituições e organizações sociais de meio mundo. Antes ainda de se ter ultrapassado a crise de confiança da última década entre os cidadãos e os governos, num momento de grande impulso das iniciativas de governo aberto e de planos de inovação e transformação digital para tornar mais democráticas e eficientes as administrações através de programas políticos encaminhados para configurar um novo contrato social, verde e digital no quadro da Agenda 2030, o coronavírus provocou um choque histórico alterando o curso do século XXI e exigindo uma aceleração de todos os processos em andamento. A complexidade e dimensão da pandemia revelou a necessidade de arquiteturas institucionais mais flexíveis, ágeis e resilientes, capazes de incorporar toda a energia civil para aprenderem com o seu talento e criatividade, dando maior protagonismo à cidadania (ativistas, empreendedores, tecido associativo, academia, makers…) não só na tomada de decisões mas também na configuração e implementação das estratégias. À medida que se afastava do centro a milhões de empregados para teletrabalhar a partir de casa, tornou-se mais poderosa a ideia de pensar nas organizações como fluxos que excedem os organigramas estáticos de lugares e pessoas. Transformar as hierarquias em redes, concebê-las como corpos sociais dinâmicos, não só alarga o seu raio de ação e conectividade externa, mas também reativa as suas forças internas, aflora as lideranças ocultas, multiplica o valor social produzido e maximiza o uso eficiente dos recursos numa época de limitações. Os laboratórios de inovação pública, social ou cidadã, ou laboratórios de governo, a par de outras formas de inovação aberta e configuração social, reivindicam-se como projetos inspiradores de uma mudança de paradigma: de instituições que ordenam para instituições que aprendem. Pensar nas organizações sob a ótica da ciência das redes e da ética dos rizomas – nós, ligações, hubs, comunidades… – deverá permitir-nos uma aproximação à complexa e subtil tarefa de configurar os ecossistemas de inovação e criatividade no âmbito público e social. Este relatório propõe um modelo denominado Hexágono da Inovação Pública (HIP) que promove uma transformação sistémica através de seis vetores (OPEN_ aberto, TRANS_ transversal, FAST_ rápido, PROTO_ modelado, CO_ colaborativo e TEC_ tecnológico) baseados nas propriedades das redes e na análise de 105 metodologias usadas pelas agências mais inovadoras do mundo. Incluem-se uma ferramenta de autodiagnóstico e o HIP-SIM, uma primeira aproximação a um software aberto para visualizar, modelar e simular a criação de ecossistemas inovadores com o qual queremos favorecer a comunidade e o debate internacional.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Mozambique / Moçambique; L - portuguese / português; M - tool / ferramenta; decentralization / descentralização; government policy / politica governamental; innovation / inovação

Guião metodológico para gestão de terras urbanas: gestão de terras urbanas municipais - República de Moçambique: Ministério do Meio Ambiente (República de Moçambique: Minitério da Terra e Ambiente, 2020)
O objectivo deste manual é auxiliar os municípios no contexto da gestão de terra, com especial foco na regularização do DUAT (Direito de Uso e Aproveitamento da Terra) e respectivas construções. O manual pretende abranger o maior número de situações que ocorrem no dia-a-dia, apresentando soluções apoiadas na presente legislação. Pretende-se que o manual seja um valioso material de apoio à capacitação das equipas técnicas dos municípios e áreas urbanas. O objectivo do manual é igualmente informar o público e capacitar os técnicos dos municípios e outras instituições com melhores técnicas e práticas para aperfeiçoar a gestão de terras de acordo com a legislação actual.
Keywords: *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; governance / governação; land governance / gestão de terra; urbanization / urbanização

Economia Política da Governação de Recursos Naturais em Nampula - Salimo, Padil (Akilizetho – ADS, 2020)
A Akilizetho-ADS elaborou um estudo denominado Economia Política da Governação dos Recursos Naturais, em Nampula. A pesquisa foi feita entre Dezembro de 2019 e Janeiro de 2020. A abordagem do estudo foi baseada numa análise de economia política e circunscrito apenas aos recursos minerais e hidrocarbonetos. O objectivo do estudo foi de compreender as relações entre governos, empresas extractivas, comunidades, sociedade civil e reflectir sobre as dinâmicas de governação da indústria extractiva e suas implicações sobre os direitos das comunidades afectadas.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; natural resources / recursos naturais

Mozambique: Analytical Report on Decentralisation - Salimo, Padil (Asociação Nacional de Municipios de Mozambique - ANAMM, EU and UCLG Africa, 2020)
The United Cities and Local Governments of Africa (UCLGA) commissioned this report in coordination with the National Association of Municipalities of Mozambique (ANAMM) to analyse the political economy of decentralisation of Mozambique. The report provides information in support of the ANAMM discussion and dialogue toward the new European Union (EU) programming process of cooperation with local authorities (LAs) for the 2021-2027 period. This report was developed in line with another called “Compendium of References” which is also part of the preparation for the EU programming process of cooperation with the Las. The analytical report on political economy pretends to explore the extent to which the central government embraced the conceptualisation of territorial development, the level of commitment of central government in recognizing the role of local authorities in the territorialisation of the national development agenda, and the opportunities and constraints created by the decentralisation system for the empowerment of local authorities as developmental actors. The political economy analysis catches the key aspects of how political and economic power influences the way how decentralisation is implemented and contested, the incentives behind the political actors and interests groups and how they impact the decentralisation reforms outcomes. The report serves as a background document to a seminar of the members of the ANAMM, which is part of a process of building consensus over the key priority action to include in the municipalities’, or interchangeably called in the report also as local authorities, roadmap for dialogue with the central government and the EU Delegation in Maputo, Mozambique. The expected result involves the following: (i) An analysis of the political economy of decentralisation, the feasibility of the new local authorities (LAs) driven political agenda and the opportunities and constraints created by the decentralisation reforms; (ii) An overview of the state of art regarding the territorialising of national policies and global agendas including SDGs, in terms of both policies and programs adopted in the framework of the national development plan; (iii) A SWOT quick analysis of the ANAMM; and (iv) The state of the art concerning the territorialisation of national policies and global programs, including Sustainable Development Goals (SDGs), both at the level of policies and programs implemented within the framework of the National Development Plan.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

Gender and countering violent extremism (CVE) in the Kenya- Mozambique region - Idris, Iffat (Institute of Development Studies, 2020)
This evidence synthesis drew on a mixture of academic and grey literature. While the literature on Kenyan women and Al-Shabaab was quite extensive (albeit with gaps, e.g. on returnees), nothing was found on women and Ansar al-Sunnah/violent extremist groups operating in northeastern Mozambique and the Mozambique-Tanzania cross-border region. This report should be read in conjunction with two earlier reviews of gender and CVE (Idris & Abdelaziz, 2017; Idris, 2019). This report builds on those – focusing on the literature on gender and CVE published since then, and on recent guidance on CVE programming – rather than reproducing their findings. This report covers three main themes: the role of women in violent extremism and in CVE (drawing on global evidence); Kenyan women’s involvement in Al-Shabaab and approaches to CVE and gender in that country; and recommendations/guidance for gender and CVE programming.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Moçambique numa encruzilhada: um diagnóstico institucional: Síntese e recomendações de política - Cruz, Antonio S; Ferreira, Ines A; Flentø, Johnny; Tarp, Finn (Economic development and institutions – Mozambique at a fork in the road: an institutional diagnostic, 2020)
Neste capítulo reunimos os diferentes elementos dos capítulos anteriores com o objectivo de apresentar a essência deste estudo sobre Moçambique. Na secção seguinte, fazemos um balanço e revisitamos os nossos pontos de partida dos Capítulos 2 e 3. Este trabalho de fundo culminou na identificação de nove áreas temáticas, posteriormente sujeitas a estudos individuais aprofundados nos Capítulos 4-12. Descrevemos as principais conclusões destes estudos e apresentamos a nossa análise integrada das principais fraquezas institucionais. Segue-se um passo decisivo, em que analisamos e discutimos as causas imediatas e os factores profundos destas fraquezas. Finalmente, terminamos com um conjunto de ideias de reforma, como contributo para a reflexão nacional, o debate e a acção.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; ⛔ No DOI found

Alcançando os mais vulneráveis na resposta da proteção social à crise da Covid-19 em Moçambique: Oportunidades e Desafios - de Lima Vieira, Ana Carolina; Vicente Andrés, Rubén; Monteiro, Denise (OIT, 2020)
O Governo de Moçambique está a responder ao impacto negativo socioeconómico da Covid-19 através da expansão do seu sistema de proteção social priorizando as populações mais vulneráveis à crise: aquelas residentes nas áreas urbanas, periurbanas e fronteiriças. Com o apoio dos parceiros de desenvolvimento, está a conseguir assegurar uma resposta política rápida, inovadora e coordenada.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; social protection / proteção social; ⛔ No DOI found

Extractive Industry Transparency Index 2019-2020 - Mapisse, Inocência; Mate, Rui; Cortez, Edson (Centro de Integridade Pública (CIP) / Public Integrity Centre, 2020)
The extractive industry, particularly the oil and gas sector, has proved promising in the Mozambican economy with potential to contribute to economic growth. It is expected that in the next 3 years the country will show growth in the order of two digits. However, in order to ensure the transmission of growth to economic development based on the exploitation of these resources, there are aspects that should not be ignored such as transparency in governance in the sector. This aspect is also recognized by the government of Mozambique through the Report on Transparency, Governance and Corruption published in July 2019, which emphasizes that the opacity in this sector can give rise to serious conflicts of interest and harm the perception of the population about the real benefits that this industry provides to the country. Although the country is part of the Extractive Industry Transparency Initiative (EITI), whose focus is on the reconciliation of payments made by companies and receipts reported by the Government in the extractive industry sector, there is a gap regarding detailed information on several aspects: tax, social, governmental and other equally relevant and that should be made available on a project-by-project basis.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; transparency / transparência

The Relationship Between Population Growth, Age Structure, Conflict, and Governance in Sub- Saharan Africa - O’Driscoll, Dylan (Institute of Development Studies, Brighton, UK, 2020)
This report addresses the relationship between population growth, age structure, and conflict in Sub-Saharan Africa (SSA). The literature reviewed for this report presents strong evidence that age structure and population growth matter for conflict. There is particularly strong evidence that points to the relationship between young age structure and conflict, although studies that disaggregate types of conflict and characteristics of young age structures (urban, male, etc.) tend to offer more robust findings. Youth bulges in particular have been associated with increased risk of conflict. The general consensus is that, in countries that will continue to experience high rates of population growth and large youth cohorts, the potential for conflict will continue to be elevated. COVID-19 is putting a dent in already weak formal employment and education. Policy responses to the pandemic will have lasting impacts for those most affected, including young people, and should therefore include them in response. The following policy recommendations are made in the literature including Patriarchal gender norms and masculinity contribute to violence and conflict, and thus policies aimed at increasing gender equality help mitigate conflict risk; The prediction that youth bulge is associated with the onset of conflict should encourage policymakers in countries with young age structures to address societal and economic inequality and foster greater inclusion of the younger cohorts into society; and Youth underemployment (and unemployment) remain an issue in SSA; bringing about structural changes that facilitate the transition into the labor market is likely to mitigate the conflict risks associated with youth bulges
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; conflict / conflito; gender / género; youth / juventude

LAND-at-Scale: Scaling Community Legal Literacy, Land Rights Certification and Climate Resilience in Mozambique - Centro Terra Viva-Estudos e Advocacia Ambiental (CTV); Firma, Terra (Rijksdienst voor Ondernemend Nederland (RVO), 2020)
The main objective of the Land at Scale Program is to increase community legal awareness and strengthen security of land tenure rights, creating capacity at local level to implement and leverage the progressive provisions of the Mozambican legal framework. The programme will contribute to community preparation to intervene in an informed manner in the land sector and will also contribute to the delimitation of community and individual land-use rights based on good faith occupation and customary rights, and their integration into the formal land system. To achieve these objectives, the proponents plan to conduct a large-scale campaign, across selected districts from all three regions of the national territory, with two main and interlinked interventions, namely: 1. Social Preparation & Legal Literacy (Component A), and 2. Community Land Rights Registration and Certification (Component B).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; governance / governação; land governance / gestão de terra

Depois da ADIN, Celso Correia “ganha” Agência do Zambeze e passa a controlar o desenvolvimento do centro e norte de Moçambique - Nuvunga, Adriano (Centro para a Democracia e Desenvolvimento (CDD), 2020)
Tal como procedeu no caso da passagem da tutela da ADIN para Celso Correia, o CDD defende que a Agência do Zambeze deve estar sob tutela do Conselho de Ministros e a sua direcção deve prestar contras ao Primeiro-Ministro. À semelhança da ADIN, a Agência do Zambeze tem uma visão holística de desenvolvimento e uma actuação transversal que abrange todos os sectores económicos e sociais do Governo, pelo que não faz sentido a sua direcção responder a um Ministro responsável por um único sector, seja ele de Economia ou de Desenvolvimento. Pela sua importância estratégica para o desenvolvimento do pontecial do Vale do Zambeze, a Agência do Zambeze deve ser dirigida por gestores de reconhecido mérito recrutados através por um concurso público transparente e independente, como forma de evitar a gestão danosa e as infracções financeiras denunciadas pelo Tribunal Administrativo em 2018. Quando o Governo de Armando Guebuza criou a Agência do Zambeze em 2010, o objectivo principal era de “assegurar a eficácia e a eficiência no desenvolvimento da parte nacional da bacia hidrográfica do Vale do Rio Zambeze, uma das regiões cujo potencial de recursos e as possibilidades de aproveitamento estudadas apontam como susceptível de, rapidamente, contribuir para o desenvolvimento e crescimento económico e humano auto-sustentado do país”. Volvidos 10 anos depois, a Agência do Zambeze ainda não deu sinais de estar a explorar as potencialidades do Vale do Zambeze para dinamizar o desenvolvimento das províncias do centro do país, que concentram boa parte da população pobre de Moçambique. O Vale do Zambeze tem potencial energético, grandes depósitos de minerais como carvão e ferro, para não falar do potencial agro-pecuário subaproveitado. Não foi por acaso que o político português Almeida Santos uma vez declarou: “Quem tem o Vale do Zambeze não pode ser um país pobre”6. Mas os cerca de 12 milhões de pessoas que vivem nas quatro províncias atravessadas pelo Vale do Zambeze continuam num vale de pobreza.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; rural development / desenvolvimento rural

The Mozambique Conflict and Deteriorating Security Situation - Bukarti, Bulama; Munasinghe, Sandun (Tony Blair Institute for Global Change, 2020)
For almost three years, the ISIS-affiliated extremist group Ansar al-Sunna has spearheaded an insurgency in Mozambique’s northern province of Cabo Delgado. In recent months the situation in Cabo Delgado has deteriorated significantly and violent attacks are now frequent. Militants have begun to target military positions having previously focused on civilian targets. It is a sign that the group is growing in resilience, operational capacity and confidence. From its first few attacks in Mocimboa de Praia in late 2017, the group now launches more than 20 attacks every month in an insurgency that covers nine major towns and districts along the Cabo Delgado coast. A battle for the town of Macomia at the end of May demonstrates the group’s organisational capacity and ambition as well as an escalation in the government’s counter-offensive efforts. On 30 May 2020, government forces engaged Ansar al-Sunna militants in one of the largest counter-terrorism operations to date, resulting in the reported deaths of 78 insurgents, including two of the group’s leaders. The extent to which this will impact Ansar al-Sunna’s operations and long-term ambitions remains to be understood.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

The Islamic State and the crises of COVID 19 - Victoria, Artur (2020)
According to the Homeland Security Today website, the statement lists "guidelines for dealing with the epidemic". For the Islamic State, the main advice is "to trust God and take refuge in Him from disease", but followers have an "obligation" to take protective measures to prevent it. Among these measures, the terrorist group emphasizes that "the healthy should not enter the land of the epidemic and the sick must not leave it". According to the council, terrorists should not travel to Europe and the United States, which are common targets in the West, nor to countries in the Middle East such as Iran, Iraq and Saudi Arabia. The group dominates provinces and has active cells in some countries still free of the disease, such as the Central and West Africa region, as well as Syria and Yemen, where civil war makes it difficult to collect information about epidemics. But cases have already been confirmed in Algeria, Egypt, Iraq, Afghanistan, India, the Philippines and Indonesia. The reorganization in Africa of ISIS - Evolution and progression in Mozambique In Mozambique, according to statements by the President of the Republic and the Minister of Defence, there are groups of terrorists in the district of Cabo Delgado and other groups in the centre, but who are considered to be affected by RENAMO. The situation is complicated because as these groups demonstrate, they show all the characteristics of IS members.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Our voices must be heard – Youth hubs discuss economic exclusion - Matsinhe, Julião (Centro para a Democracia e Desenvolvimento, 2020)
Youth hubs discuss economic exclusion. Unemployment was singled out as the most pressing challenge that young people face. As an answer to unemployment, these young people highlighted that education must equip students with relevant skills to be innovative and entrepreneurs, and to be competitive in the labor market.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Face ao conflito no norte, o que Moçambique pode aprender da sua própria guerra civil (1976 – 1992)?: Uma análise das dinâmicas da insurgência em Cabo Delgado - Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Analisa as dinâmicas da insurgência em Cabo Delgado e procura interrogar o que Moçambique pode aprender dos seus ciclos de violência armada, particularmente a guerra civil, para fazer face ao actual conflito no Norte do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Republic of Mozambique Joint World Bank-IMF Debt Sustainability Analysis - IDA; IMF (International Development Association (IDA) and the International Monetary Fund (IMF), 2020)
Mozambique’s debt remains in distress, which is unchanged from the previous DSA published in June 2019. Consideringthat, to a large extent, future borrowingand governmentguarantees reflect state participation in the sizable liquified natural gas (LNG) development, debt is deemed sustainable in a forward-looking sense. Participation in the recently announced G20 initiative would provide debt service relief in the near term, thus flattening the projected sharp deterioration in debt liquidity indicators due to the COVID-19 pandemic. The possibility of an extension of the G20 initiative into 2021 would be a further mitigating factor for the debt sustainability assessment. The present value (PV) of external public and publicly guaranteed (PPG) debt relative to GDP is projected to remain above the prudent threshold with a gradual declining path dropping below the threshold by 2028.The PV of PPG external debt relative to exports would drop below the prudent threshold in 2024. The ratio of external public debt service to fiscal revenues would drop below the prudent threshold temporarily in 2020 but would breach again the threshold until 2030. The debt service-to-exports ratio would remain around the prudent threshold until 2023, when it drops and remains below the threshold for the rest of the projection period.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; economic development / desenvolvimento económico

Unpacking the Potential Socioeconomic Impact of the Coronavirus Pandemic in Mozambique: A United Nations Situation Analysis and Policy Recommendations - United Nations Mozambique (United Nations, 2020)
The Coronavirus pandemic arrives in Mozambique at a time when, after several years of modest economic performance, the Mozambican economy was starting to show signs of recovery. Hence, the latest projections of the IMF of November 2019 had the Mozambican economy growing at 6% in 2020, with medium term projections reaching 9% and above after 2023, following the initiation of LNG exploration operations in the north of the country. Despite this improving macroeconomic outlook prior to the outbreak of the Coronavirus pandemic, living conditions for many Mozambicans remain harsh. Poverty afflicts almost half of the population, 46.1% according to the 2014/15 national household survey, and many people continue without access to basic services, with the proportion of Mozambicans with access to basic water supply, basic sanitation and electricity remaining at very low levels: 55.7%, 29.4% and 27.4% in 2017, respectively. Moreover, despite improvements in healthcare conditions, Mozambicans, especially women and children, continue to be severely afflicted by disease and sickness. In general, living conditions tend to be worse in rural than in urban parts of the country. The coronavirus pandemic is almost certainly going to change this short- and medium-term economic outlook and could potentially have a very significant socioeconomic impact in Mozambique. However, while all available evidence points in this direction, at this stage it is difficult to ascertain and quantify the extent of this impact, given the speed at which things are changing around the world and the uncertainly surrounding the epidemiological profile of the Coronavirus, which makes it hard to assess how long the containment and lockdown measures being applied around the world will need to remain in place. While a detailed quantification of the socioeconomic impact of the coronavirus pandemic may not be feasible, it is still useful to identify possible transmission channels through which the pandemic may affect the Mozambican economy and society. It is also useful to identify key issues that are likely shape shortand medium-term socioeconomic prospects in Mozambique as a result of the Coronavirus pandemic outbreak in Mozambique. The following sections outline some of these.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde

General Elections 15 Oct 2019 Final Report - Hanlon, Joseph; Cortez, Edson; Nhancale, Sheila; Mendonça, Magda; Bande, Aldemiro; Nhacume, Nelia; Mahiquene, Telma (Mozambique Political Process Bulletin 58, 2020)
Frelimo and President Filipe Nyusi swept away the opposition in the 15 October 2019 general elections, matching Armando Guebuza's 2009 landslide. But there were widespead reports of misconduct. On a 52% turnout, Nyusi won 73% of the vote with over 50% in all provinces. Frelimo won majorities in all provincial parliaments and in the first ever election of governors, Frelimo won all ten.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; electoral geography / geografia eleitoral

Protecção social em contexto de terrorismo: que implicações tem a insurgência islâmica nos mecanismos formais de protecção social em Moçambique? - Siúta, Moisés (IDeIAS, 2020)
O impacto do terrorismo em Moçambique é uma realidade que não se restringe apenas à zona Norte do país. O IDeIAS nº 137, da autoria de Moisés Siúta, procura discutir as suas implicações nos sistemas formais de protecção social tendo em conta o desafio que enfrentam de garantir protecção e bem-estar social da população nas regiões mais afectadas sem, no entanto, deixar para trás a população vulnerável a diversos riscos como seca, cheias e a pandemia.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito; social protection / proteção social; ⛔ No DOI found

Baseline Assessment of Facility and District Capacity: Alcançar Qualidade de Serviços de Saúde para Mulheres e Crianças - USAID; fhi360; Alcançar (FHI 360, 2020)
The Alcançar Baseline Assessment of Facility and District Capacity was conducted to establish an evidence base against which to measure project performance and impact over the life of the project and to inform project priorities and planning. The assessment includes a census of health centers and hospitals in Nampula province - the population of facilities that the project is expected to influence. Trained data collection teams interviewed facility and district staff to collect current information on (1) facility infrastructure and policies, (2) human resources, (3) ordering and management of maternal and child health (MCH) commodities, (4) provision of MCH services (5) knowledge of MCH care components, and (6) emergency referral capacity. Additionally, they reviewed and extracted data from facility registers over a 6-month period and observed antenatal care (ANC) consultations. Data collectors visited each of the district health offices (Serviço Distrital de Saúde, Género, Criança e Acção Social, SDSMAS) to gather information on district health capacity to provide clinical mentoring, implement quality improvement and death audits, and manage commodities. This assessment report presents selected results.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; health - maternal and child / saúde - materno-infantil; health / saúde

Economic brief - The Africa Infrastructure Development Index (AIDI) 2020 - African Development Bank (African Development Bank, 2020)
The development of infrastructure in Africa is critical for fostering economic growth and improving the living standards of Africans. It contributes significantly to human development, poverty reduction, and the attainment of the Sustainable Development Goals (SDGs). Investment in infrastructure accounts for over half of the improvements in economic growth in Africa witnessed over the last decade and has the potential to contribute much more, given a conducive environment.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Mozambique - Invest in the Energy Sector of Mozambique - African Oil and Power (Africa Energy Series, 2020)
Since initial exploratory drilling in 2007 by U.S. operator Anadarko, Mozambique has uncovered vast natural gas volumes within its offshore basins, and now carries the potential to be the fourth largest natural gas exporter globally. With discoveries ranging from Anadarko’s initial 480 feet of gas found in Area 1 in 2010, to Eni’s discovery of 425 billion cubic meters one year later, the onus now lies on major operators including Royal Dutch Shell, Total, Eni and more to develop the requisite infrastructure to exploit the reserves, generate exports and bring revenue into the country. Potential inhibitors to the development of such resources include two ‘black swan’ events that have occurred since early-2020. In addition to the onset of COVID-19 in March – including a specific outbreak on Total’s Mozambique LNG development – the gas-rich Cabo Delgado province is facing a growing Islamist insurgency that began in the country in 2017. Nevertheless, the world-class nature of Mozambique’s gas assets has offset such inhibitors, and the country recently secured the largest foreign direct investment in Africa to date through its Mozambique LNG development. Gas monetization projects push forward on schedule, as the nation continues on its path to becoming a global energy giant.
Keywords: G - Mozambique / Moçambique; L - english / inglês; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

BTI 2020 Mozambique Country Report - BTI (2020)
“Mozambique faces five major challenges: violence between political camps, impunity with regard to corruption, violations of human rights, the debt crisis and the security threat of Islamist terrorism.”
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Niassa, Mozambique: The Makhuwa-Shirima and Yao Peoples - Center for the Study of Global Christianity (Gordon-Conwell Theological Seminary, 2020)
The region of modern-day Mozambique has always been strategic for global trade. Since at least the medieval period its coasts have been visited by traders from India, Somalia, Ethiopia, and beyond. Portuguese explorer Vasco da Gama arrived in 1498, marking the beginning of nearly 500 years of Portuguese colonial rule of the territory. Mozambique achieved independence from Portugal in 1975, but subsequently experienced a series of civil wars from 1977 to 1992. Democratic elections in 1994 resulted in a relatively stable modern republic. Despite the history of power struggles, Mozambique’s indigenous population, which include the Yao and the Makhuwa-Shirima peoples, carries with it a unique legacy challenged by colonialism and trade. To the present-day, these peoples maintain a presence in Mozambique; albeit, one that is continually threatened by cultural imperialism and globalization. The Yao (also, Wayao) people, many of whom live in Niassa province, largely rejected foreign colonial rule and the Christianity associated with it. Islam, introduced by Arab traders, was perceived a better cultural fit for the Yao and allowed for greater economic opportunities in light of the extant slave trade that ran through the Lake Niassa region and along the Rovuma River. As a result, the Yao were quite prosperous. Famous Scottish pioneer missionary-explorer David Livingstone passed through Niassa in search of the most direct route to the African interior. One of his most trusted African colleagues was a Yao man.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; society / sociedade

Estudo de caso: Cabo Delgado (Moçambique). A terra onde não se come o que se produz e produz o que não se come - Cunha, Teresa; José, André Cristiano; Monjane, Boaventura; Bidaurratzaga, Eduardo; Casimiro, Isabel; Trindade, João Carlos; Alberdi, Jokin; Cruz, Lucinda; Valle, Luísa de Pinho (Gernika Gogoratuz, 2020)
No final do seminário e das oficinas-grupos de trabalho procedeuse a um debate aberto para partilha das reflexões e identificação de conclusões principais: • A participação em espaços de consulta/decisão está muito condicionada pela falta de conhecimentos de quem participa, mas também pela falta de transparência e assimetria da informação. • A exclusão social está na base da pouca ou fraca participação e monitoria. • A qualidade da monitoria nos processos de governação e desenvolvimento é fraca. • A monitoria da governação e desenvolvimento é vista pelos poderes como «acções-sombra» ou «mandatados da oposição». • Os governantes têm medo de falar de desenvolvimento com a cidadania. Preferem discutir questões do partido. • Existem poucos espaços de participação criados e também reclamados. • Existe uma confusão de papéis e das suas compatibilidades entre as lideranças e a administração. • Não se aplica a lei, em muitos casos. • Existem lideranças reconhecidas e não reconhecidas. • Algumas iniciativas começam a ter os seus resultados na província, sobretudo no contexto urbano e relacionadas com grupos de jovens. • Algumas organizações da sociedade civil reproduzem dinâmicas de poder e definem o que é ou não prioritário para as comunidades (nos seus gabinetes). • Também existe corrupção e fraca prestação de contas entre as organizações da sociedade civil, não só na Administração/Governo. • Os jovens de Cabo Delgado necessitam ter formação e emprego nos grandes projectos de desenvolvimento.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; agriculture / agricultura; conflict - civil war / conflito - guerra civil; conflict / conflito

Análise de Economia Política da Governação Local Moçambique - Eurosis (Mozambique Monitoring and Evaluation Mechanism and Services (MMEMS), 2020)
A governação local em Moçambique continua a desenvolver-se em duas vertentes: a desconcentração de poderes, através dos órgãos locais do Estado (secretarias de Estado da província, administrações distritais, etc), e a devolução do poder através dos órgãos de poder local (presidentes de conselhos autárquicos e governadores provinciais eleitos). O processo de criação de autarquias tem sido muito lento e a maioria dos cidadãos vive em áreas geridas pelos órgãos locais do estado e não por órgãos eleitos directamente por si. Não é ainda claro como vai funcionar a administração pública no novo figurino que criou a representação do Estado nas províncias onde existem governadores eleitos e um governo estabelecido. O que é claro, é a forte tendência para a centralização do partido político no poder e para a intervenção directa na gestão local da coisa pública, o que afecta a inclusão, transparência e prestação de contas em todas as áreas de governação. O quadro de políticas e legal é disperso e omisso em relação a como se realiza a participação dos cidadãos e cidadãs na governação em geral e como se promove a inclusão, transparência e prestação de contas. É também limitado o quadro em que operam serviços fundamentais para a transparência da administração pública, como por exemplo, os serviços de inspecção de saúde e educação, cujo quadro regulatório limita o potencial destas intervenções. Este contexto cria oportunidades para o exercício de poder discricionário a todos os níveis e leva a que intervenções fiquem dependentes do interesse político dos líderes aos vários níveis para a sua implementação. Num contexto de uma corrupção generalizada, isto é um obstáculo à realização de actividades e sustentabilidade das intervenções. Apesar das limitações apontadas, existem oportunidades e espaços para promover uma maior participação dos cidadãos e melhor prestação de contas do sector público, os quais podem ser usados como base para novas intervenções. Assim, apesar da ausência de um bom quadro legal, há alguma legislação e posições públicas do governo que remetem para um primado do cidadão, para um serviço público de qualidade e inclusivo e para o combate à corrupção. Há também mecanismos e processos que assumem a participação informada dos cidadãos nos processos de decisão sobre questões do desenvolvimento em geral (IPCC, assembleias autárquicas e provinciais) e da saúde e educação em particular (comités das unidades de serviços). Existem formalmente instituições e processos que têm como função garantir uma administração pública isenta e de qualidade (inspecção, tribunais administrativos provinciais, gabinetes anticorrupção). O nível de funcionamento destes mecanismos e processos varia muito e está dependente do interesse dos governantes locais, da mobilização comunitária e dos recursos existentes). Assim, pode dizer-se que há uma base para sobre a qual trabalhar para conseguir mais transparência, prestação de contas e inclusão ao fortalecer a governação local ao nível provincial, distrital e local (da unidades de prestação se serviços). Também o apoio à inspecção de saúde e educação pode contribuir para a melhoria da qualidade de serviços prestados aos cidadãos ao assegurar um melhor seguimento das regras e protocolos de prestação de serviços. É importante notar, contudo, que para além dos obstáculos acima referidos, o presente momento coloca desafios particulares ao desviar a atenção do governo para a resposta aos conflitos armados e à pandemia do COVID-19.
Keywords: *non-public; *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; GP - Nampula; GP - Zambézia; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; education / educação; governance / governação; health / saúde; institutions / instituições

A4EA Insights: Country briefing on Mozambique - IDS (IDS, 2020)
The Action for Empowerment and Accountability Research Programme (A4EA) examines different forms of social and political action to understand how and under what conditions they contribute to real world change, including gains in empowerment for the most excluded and marginalised, and for increased accountability of authorities. A4EA work is highly relevant to FCDO’s expressed goals of developing research-led solutions to building open societies and supporting conflict resolution, including through a focus on strengthening democratic institutions, human rights and effective, accountable governance. In Mozambique, A4EA projects include long-term work to understand poor and marginalised people’s experiences of different authorities, in-depth research on the dynamics of protest and claims for accountability and better services in a range of key sectors including energy and transport, exploration of women’s leadership and representation, and analysis of donor governance programmes. Working with a range of Mozambican research partners including the Instituto de Estudos Sociais e Económicos (IESE), Kaleidoscopio, Fórum Mulher and the Centro de Integridade Pública (CIP) we have completed six A4EA projects that included research in Mozambique, and have five studies currently ongoing.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês

Anuário Estatístico da Província de Nampula 2019 - INE (Instituto Nacional de Estatística, Governo de Moçambique, 2020)
O Anuário Estatístico da Província de Nampula 2019 é uma publicação estatística de carácter geral que a Delegação do Instituto Nacional de Estatística em Nampula leva aos utilizadores e ao público em geral, como um vínculo para a disseminação dos principais indicadores económicos, sociais e demográficos da Província.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Anuário Estatístico - Statistical Yearbook 2019 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2020)
À semelhança das edições anteriores, o Anuário Estatístico 2019 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios. O mesmo constitui parte da série de publicações que o Instituto Nacional de Estatística (INE), na sua missão de proporcionar, à sociedade moçambicana, informação estatística que permita o conhecimento da realidade do País, disponibiliza aos utilizadores e ao público em geral, como um veículo para a disseminação dos principais dados económicos, sociais e demográficos de Moçambique, na sua maioria, na série 2015-2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; L - portuguese / português; Northern PEA; demographics / demografia

Indicadores Básicos de Agricultura e Alimentação 2015-2019 - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística (INE), 2020)
1. Esta publicação apresenta os indicadores básicos de agricultura e alimentação dos últimos 5 anos, como alternativa da base de dados na plataforma online “countryStat” produzida com fontes administrativas, mas descontinuada em 2019. A publicação não abrange todos indicadores cobertos como desejado, porque alguns requerem harmonização metodológica e outros ainda não são produzidos com regularidade pelos sectores. 2. A compilação desta publicação baseou-se na recolha e tratamento preliminar das bases de dados disponibilizadas pelas fontes administrativas dos sectores. A seguir, a equipa de produção fez a limpeza e validação de dados, resultando na publicação com 10 grupos de indicadores. 3. Nos indicadores socio-demográficos, destaca-se a população de Moçambique, como principal activo da produção, ao atingir a magnitude de 29,3 milhões de habitantes em 2019, 66,2% da qual vivia na área rural, e continuando concentrada em Nampula e Zambézia com 6,03 e 5,43 milhões de habitantes respectivamente. 4. O segundo indicador refere-se à insegurança alimentar aguda, cujo resultado indica um grande agravamento, ao partir de 3,6% em 2013 para 29,9% de famílias em 2019, um comportamento assumido também pela desnutrição aguda em crianças que de 1,9% em 2013 deteriorou-se para 12,3% em 2019. 5. Nos indicadores económicos, ressalta o peso do PIB do sector agrário a preços constantes, ano base de 2014, que estabilizou-se em torno de 23%, entre 2015 e 2019, tendo a respectiva taxa de crescimento registado 1,2% em 2019, abaixo da média nacional que foi de 2,3% face a 2018. O orçamento do estado alocado ao sector continuou abaixo de 10% em todo quinquénio, tendo-se fixado em 4,9% em 2019 6. A mecanização agrícola, medida pelo número de tractores alocados pelo Fundo do Desenvolvimento Agrário ao sector privado para agricultura familiar, reduziu, ao partir de 361 em 2015 para 26 unidades em 2019. No entanto, a área lavrada pelos provedores deste serviço e os produtores beneficiados aumentaram 97% e 781% respectivamente entre 2015 e 2019. 7. O crédito concedido ao sector agrário manteve-se insignificante se comparado com o resto da economia ao corresponder a um peso de 3,65% em 2015 e 3,71% em 2019. 8. A produção per capita de cereais continuou baixa para garantir a segurança alimentar, ao registar 71(Kg/hab) em 2015 e 94,3 kg em 2019. Para mandioca e batata doce, a situação continuou bem e melhor com a produção per capita de 267 kg em 2015 e 336 kg em 2019. A produção das culturas de rendimento foi estável no período de referência, facto observado nas mudas de cajueiros produzidas em torno de 4,5 milhões em 2019. Os produtos pecuários apresentaram, ao longo do quinquério, valores per capita baixos. Com efeito, a carne de frango registou uma produção per capita de 3,8 kg em 2019, partindo de 2,5 kg em 2015. Na produção de carne bovina, destacou-se a Província de Maputo com quase a metade da produção do País, 7 266 toneladas em 2019. Manica e Sofala destacaram-se na produção de leite de vaca ao deter 41,3 % e 25,1 % do total em 2019, respectivamente. A produção de pescado per capita caiu para 11,6 em 2019, depois de 13,7 kg em 2018 e 12,4 kg em 2017. Contudo, ressalta-se a produção de peixe marinho com 177 071 toneladas em 2019 correspondentes a 59,5% de toda a produção do sector. 9. No comércio externo, evidencia-se a exportação de açúcar e produtos de confeitaria, com crescimento de 22,9% da contribuição na receita aduaneira de 2019.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - indicators / indicadores; Northern PEA; agriculture / agricultura

Plano de monitoria e avaliacao dos programas de seguranca social basica - Macamo; Malôa, Chessira; Bazo, Geral; Mataba, Gito; Naene, Hélder; Maússe, Miguel; Machume, Olga; Monteiro, Vanádio (Instituto Nacional de Acção Social (INAS), 2020)
O presente documento foi desenvolvido pela equipa técnica do Instituto Nacional de Acção Social (INAS), com apoio técnico e financeiro da Organização Internacional do Trabalho (OIT) como resultado de acções promovidas pelo Sector no desenvolvimento e implantação de um modelo prático, eficiente e eficaz de Monitoria e Avaliação para os programas de Segurança Social Básica. O Plano de Monitoria e Avaliação dos programas de segurança social básica geridos pelo INAS obedece à Acção Estratégica número 33 do Plano Operacional da ENSSB 2016-2024, que visa “Operacionalizar o novo Sistema de Monitoria e Avaliação (M&A) do INAS e concluir o desenvolvimento de um sistema de M&A mais abrangente para o Subsistema de Segurança Social Básica”. Neste contexto, e à luz do Decreto 63/2018 de 26 de Junho, o INAS, IP criou na sua estrutura orgânica a Repartição Central de Monitoria e Avaliação para reforçar a sua capacidade ao nível nacional. As acções que culminaram com a elaboração do plano obedeceram uma metodologia prática e objectiva na medida que além de promoção de sessões de formação, sessões de debate e definição de quadros de monitoria e avaliação, foi também realizado um estudo ou análise que permitiu a definição de um RoadMap de M&E para os Programas de Segurança Social Básica implementados pelo Instituto Nacional de Acção Social. Como o presente documento consolida-se assim um instrumento unificado para guiar de forma prática as acções de M&A de todos Programas de Segurança Social Básica implementados pelo INAS até 2024. Este documento foi igualmente inspirado no modelo de Sistema de M&A do curriculum TRANSFORM, o que permitiu não só a definição do modelo apresentado no presente documento, mas também contribuiu consideravelmente na definição de uma periodicidade de revisão e melhoria do modelo, atendendo ao facto do presente modelo ser novo para o INAS tanto ao nível central como a nível das Delegações. O presente plano, aborda de forma detalhada a M&A os indicadores inerentes a cadeia de processos incluindo o pagamento terceirizado das transferências monetárias no PASD-PE e do PSSB incluindo a componente PSSB-SC tendo em conta todas fases de implementação.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; M - evaluation / avaliação; Social security / segurança social; social protection / proteção social

Análise do Plano Económico e Social e Orçamento do Estado de 2020 nas Áreas da Saúde, Água e Saneamento - Marrengula, Constantino (Forum de Monitoria do Orçamento, FMO Mais, PAANE, 2020)
Os objectivos e os pilares do PES e OE de 2020 não mudaram, substancialmente, em comparação com o que foram as prioridades do quinquênio 2015-2019. Em linha com os compromissos internacionais, o Governo procurou manter os pesos relativos da despesa nos sectores prioritários, com particular realce para a educação e a saúde. Contudo, o aumento dos preços e dos encargos da dívida, que se seguiu à descoberta das dívidas não declaradas, baixou o valor real das provisões feitas nestes sectores. O valor de cerca de 26 mil milhões de Meticais reservado para a saúde em 2020 representa uma redução em relação ao que tinha sido programado para 2019, não obstante os desafios impostos pela pandemia da Covid19. A redução em termos reais do orçamento da saúde, ocorre num quadro geral, em que todas as metas previstas para o quinquênio passado foram revistas em baixa, ou não foram cumpridas. Por exemplo, num ano eleitoral como foi 2019, a taxa de realização da meta de recrutamento de profissionais para o sistema nacional da saúde situou-se em volta de 50%. As metas do PES e OE 2020 da saúde não parecem suficientes para que o sector recupere dos incumprimentos do quinquênio passado, num contexto que conta com a pandemia da Covid-19. Para o sector de água e saneamento, os acordos assinados com o Exim Bank da Índia, o Banco Mundial, e a SADC deram um novo impulso ao Programa PRAVIDA, mas o nível de realização das metas do PES e do orçamento do sector não foi substancialmente diferente do que aconteceu na saúde. Quando o orçamento aumentou em 2019 a taxa de execução do orçamento baixou para 32%, com incumprimentos em intervenções com impacto directo na pobreza, tanto rural como na zona peri-urbana. A revisão em baixa das metas do PES de 2020, em comparação com o definido para 2019, alarga o tempo necessário para que a intervenção do Estado no sector faça a diferença no acesso à água e saneamento. Num cenário de crescimento populacional, quanto mais conservadora e lenta for a intervenção maior é o atraso na correcção dos problemas identificados, o que certamente tem implicações na materialização dos objetivos de desenvolvimento sustentável. Reverter o cenário que sustenta as taxas de execução sub-óptimas dos orçamentos aprovados e a queda em termos reais das disponibilidades nos sectores prioritários constitui o principal desafio das Finanças Públicas em Moçambique. Embora não esteja claro o que poderá ser o futuro destes sectores depois da pandemia da Covid-19, a curto prazo torna-se importante encontrar formas de usar melhor o que se tem, retomar a trajectoria de sustentabilidade da dívida pública e normalizar as relações com os principais parceiros de apoio orçamental. Como se pode perceber da dinâmica dos indicadores da saúde, água e saneamento, os custos sociais de sub-utilizar o potencial existente e manter o status quo nas Finanças Públicas são demasiado altos para serem desconsiderados.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health - WASH / saúde - água, higiene e saneamento; health / saúde

A Pharmaceutical Logistics still far from answering health concerns of the country: budgetary weaknesses - N'weti (N'weti, 2020)
Key Messages: - Pharmaceutical logistics make up only 7% of total projected costs for the health sector through 2019; - The expansion and demand of the health sector in the forthcoming years will not be accompanied by the necessary increase in resources for the pharmaceutical logistics sector; - Increased nancing in the area of PL is necessary, preferably from internal sources, to allow the implementation of PELF recommendations; - It is estimated that 13% of the value of the approximately $3,929 million needed to procure and manage drugs and commodities during 2014-2019 will be wasted. - The health sector is heavily reliant on external funding, with 81% of funding for medicines comming from external partners; - There is concerning public evidence of systematic stock-outs of medicines in public pharmacies throughout the country. Research by Nweti (2014-2015) in 37 health acilities in four provinces using the community score card as a survey tool, found that stock-out of essential medicines was one of the barriers to accessing quality health services. Another study carried out by Wagenaar, et al. (2014) in Sofala Province, which assessed 26 facilities showed that only one out of the 26 facilities assessed in 2011, 2012, and 2013 had all of the 15 essential medicines.
Keywords: G - Mozambique / Moçambique; L - english / inglês; budget / orçamento; health / saúde

Uma Logística Farmacêutica ainda distante de responder às preocupações de saúde do país: as fragilidades orçamentais - N'weti (N'weti, 2020)
A área de logística farmacêutica (LF) é vital pelo facto de assegurar que os medicamentos e produtos médicos estejam disponíveis no país e nos pontos de entrega e inclui seleção de medicamentos, quanti cação, procurement, controle de qualidade, armazenamento, transporte e distribuição. O Governo de Moçambique reconhece a importância deste sector e como parte da agenda de reforma do MISAU desenhou o Plano Estratégico de Logística Farmacêutica (PELF) juntamente com o respectivo Plano Operacional (2013). O PELF visa responder a necessidade de providenciar reformas a área de logística farmacêutica melhorando a gestão nanceira, procurement, inventariação, gestão do armazenamento, transporte, distribuição, uso de medicamentos e gestão de recursos humanos. Relatórios disponíveis apontam para a existência de vários desafios na implementação do PELF sendo que a falta de recursos financeiros é um dos maiores desafios para a implementação do quadro de recomendações deste documento. Em Moçambique a LF é actualmente uma das áreas menos favorecidas em termos de dotação orçamental cabendo-lhe 7% do total de envelope de recursos do sector da saúde projectados até 2019 (MISAU/DNPC, 2013). Esta tendência ao ser estacionária ao longo dos próximos 5 anos certamente estará em descompasso com a expansão e aumento da demanda pelos serviços públicos de saúde o que poderá comprometer a prestação do sector de saúde. A actual fonte de nanciamento e práticas de alocação orçamental na área de LF é também problemática. A estimativa da taxa de desperdício de medicamentos e consumíveis representa cerca de 13% do investimento total de $3,929 milhões de dólares da área de Logística Farmacêutica. Uma redução da taxa de desperdício para 5% implicaria numa economia de 332 milhões de dólares durante o PESS 2014 - 2019 (Dutta et al., 2014). Adicionalmente mais de 81% dos fundos para área de medicamentos são nanciados por parceiros externos (Dutta et al., 2014). Esta dependência de fundos externos é preocupante num cenário de incerteza do nanciamento externo ao sector de saúde (Dutta et al., 2014). Os níveis de satisfação da disponibilidade de medicamentos essenciais a nível central apesar de registarem progressos contrastam com a disponibilidade de medicamentos a nível das unidades sanitárias (MISAU, 2013, 2014). Várias Organizações da Sociedade Civil (OSC) incluindo a N ́weti, MSF o CIP tem denunciado sistemáticas rupturas de medicamentos nas unidades sanitárias das províncias do sul, centro e norte do país. Face as rupturas sistemáticas de medicamentos nas unidades sanitárias e a imprevisibilidade do nanciamento externo é crucial que o Governo de Moçambique incremente o volume de nanciamento para a área de LF sobretudo na base de recursos domésticos. A falta de recursos está a afectar grandemente a implementação do PELF e de igual modo a capacidade do sector de saúde em providenciar de forma e ciente serviços de saúde de qualidade.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; health / saúde

Measuring Governance, Advocacy and Power: A Database of Existing Indicators, Tools and Indices - Poirrier, Caroline; Tolmie, Courtney (R4D, 2020)
Measuring Governance, Advocacy, and Power is an excel sheet that brings together existing indicators, tools, and indices that may be useful to practitioners responsible for the measurement of outcomes in the field of governance, advocacy, and power in an easily accessible and filterable format.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; L - english / inglês; M - indicators / indicadores; M - tool / ferramenta; governance / governação

Democracy Index 2020 In sickness and in health? - The Economist Intelligence Unit (The Economist, 2020)
The main focus of the report is the impact of the coronavirus (Covid-19) pandemic on democracy and freedom around the world. It looks at how the pandemic resulted in the withdrawal of civil liberties on a massive scale and fuelled an existing trend of intolerance and censorship of dissenting opinion (see page 14). The report also examines the state of US democracy after a tumultuous year dominated by the coronavirus pandemic, the Black Lives Matter movement and a hotly contested presidential election (see page 42). The results by region are analysed in greater detail in the section entitled “Democracy around the regions in 2020” (see page 26).
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; civil society / sociedade civil; health - COVID-19 / saúde – COVID-19

Informe Orçamental Acção Social - Mozambique 2020 - UNICEF (UNICEF and Organização Internacional do Trabalho (OIT), 2020)
Principais Mensagens: 1. Apesar do aumento contínuo registado na dotação orçamental destinada à protecção social desde 2010, o nível do espaço fiscal dedicado aos programas de protecção social básica (não contributiva) ainda está aquém das necessidades e, a menos que seja consideravelmente melhorado, é pouco provável que o sistema cumpra a meta estabelecida na ENSSB 2016-2024 (2,23 por cento do PIB). 2. A cobertura específica dos programas de Protecção Social definidos no PQG 2015-2019 não foi cumprida em resultado de dotações sectoriais insuficientes, bem como de ineficiências na execução orçamental. Com o impacto negativo da COVID-19 na renda da população moçambicana, as necessidades de protecção social são maiores do que nunca. Por conseguinte, é ainda mais necessária uma rápida expansão da cobertura, e consequentemente, torna-se necessário proceder a uma dotação orçamental muito maior para 2020 e 2021. 3. O apoio orçamental dos principais doadores (tais como o Banco Mundial e outros) constitui uma importante oportunidade para o sector da Protecção Social cumprir os ambiciosos objectivos de expansão da cobertura. É necessário um mecanismo sólido de monitoria, informação e prestação de contas que garanta o acesso aos recursos, pelo que uma utilização eficaz do e-INAS poderia ser a solução-chave. 4. Embora seja atribuída uma maior dotação orçamental às províncias com maior índice de pobreza / vulnerabilidades, uma grande lacuna ainda está por preencher. No orçamento de 2020, a dotação per capita (por pessoa pobre) nas províncias desfavorecidas do Norte é muito mais baixa do que a das províncias relativamente mais ricas do Sul. Como forma de reduzir a desigualdade, é necessária uma expansão da cobertura, bem como a priorização de áreas com taxas de pobreza mais elevadas.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; social action / ação social; social protection / proteção social

State Budget Proposal for Fiscal Year 2020 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2020)
Key messages: 1. The value of the State Budget for 2020 is MT 345.4 b. The 2020 State Budget marks the beginning of a new governance cycle (2020-2024) and is aligned with the strategic objectives and priorities defined in the new 5-year plan (PQG 2020-2024). However, the current global COVID19-induced economic uncertainty has led the Government of Mozambique to a restrictive approach to the budget aimed at prioritizing the provision of basic services to the population. 2. The Council of Ministry’s Decree n.2/2020 established the principles and norms of the provincial decentralized governance, both political and financial. However, this was not yet reflected in 2020 State Budget. 3. The government’s new overarching development strategy, the “Government’s Five-Year Plan (PQG 2020-2024)” has 3 strategic priorities and 3 strategic pillars. In the 2020 State Budget, Priority II: Promote Economic Growth, Productivity and Job Creation, received the majority of funding, worth 44 percent of budget. Priority I: Develop Human Capital and Social Justice was allocated 35 percent of 2020 State Budget resources. 4. This year the Government has prioritized the allocation of resources to essential sectors, namely Health, Education and Agriculture & Rural Development. The allocation to these three sectors is worth 48 percent of 2020 State Budget (excluding debt servicing and financial operations) or 34 percent of the entire budget. Relative to last year, the allocation to the Education sector increased while those of the Health and Agriculture sectors decreased. 5. In the 2020-2024 PQG, the Government set the goal of allocating 65.2 percent of resources to priority economic and social sectors. This year’s cumulative allocation to priority areas is worth 68 percent of the State Budget less financial operations and debt servicing, or 48 percent of the entire State Budget including financial operations and debt servicing. Of the priority Economic and Social sectors supported by UNICEF, Education was allocated Meticals (MT) 66.3 billions (b), Health MT 26.7 b, Social Action MT 6.7 b and WASH MT 7.1 b in the State Budget for 2020. 6. The allocation to Education increased by 17 percent in nominal terms and by 9 percent in real terms relative to 2019 Budget. The sector allocation is worth 19.2 percent of 2020 State Budget. Excluding financial operations and debt servicing, education represents 27.1 percent. As a share of Mozambique’s GDP, the Education sector’ allocation represents 6.1 percent. 7. The Health allocation represents a 5 percent nominal decrease and an 11 percent real terms-decrease compared to last year’s budget. Such decrease is explained by the heavy reduction in externally-funded on-budget resources to the sector. Health is worth 7.7 percent of the 2020 budget. Excluding financial operations and debt servicing, the sector represents 10.9 percent. As a share of the expected GDP for 2020, the Health Budget is worth approximately 2.5 percent. Relative to last year, the sector allocations decreased both as a share of government expenditure and as a share of GDP. 8. The Ministry of Health has developed a National Plan for COVID-19 preparedness and response which will be allocated approximately MT 1.8 b or USD 28.4 m through off-budget resources, of which 56 percent will be allocated to drugs and supplies. The Ministry of Health COVID-19 Plan however does not include budget for water services and hygiene measures essential to Infection prevention and control (IPC). 9. The 2020 initial allocation to Social Action dropped by 7 percent in nominal terms and by 14 percent in real terms compared to 2019. However, spending for INAS Social Protection Programs as a share of budget and as a share of GDP is on par with those of last year. Still, given the risk of increased vulnerabilities due to COVID-19, larger allocations to INAS programs are recommended.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento

Vampiros, Jihadistas e Violência Estrutural em Moçambique: Reflexões sobre Manifestações Violentas de Descontentamento Local e as suas Implicações para a Construção da Paz - Weimer, Bernhard (Cadernos IESE, 2020)
Este ensaio, escrito em Março de 2018, procura explicar, numa perspectiva histórica, ataques violentos recentemente perpetrados contra instituições locais e representantes do Estado moçambicano. São usados estudos de caso de três províncias moçambicanas, aos quais se acrescentam casos históricos de ataques armados com padrões e alvos semelhantes. Com base em investigação documental, entrevistas e análise da literatura de Antropologia e Economia Política, são identificadas três causas principais dos conflitos locais – todos eles com os seus contextos e narrativas específicos: em primeiro lugar, a economia política com raízes históricas, dominada pela Frelimo, lida com o descontentamento e a divergência de forma autoritária e muitas vezes violenta, ou, nas palavras do antropólogo Bjørn Bertelsen, com «guerra como governação»; Em segundo lugar, a Ordem de Acesso Limitado firmemente estabelecida em Moçambique produz a exclusão socioeconómica de intervenientes e interesses sociais, económicos e políticos locais, nomeadamente quando se relaciona com extracção de recursos naturais; e um terceiro factor é uma perspectiva de que «não há futuro» da juventude moçambicana, a maioria demográfica. Presa numa idade da espera (waithood, Alcinda Honwana), esta juventude está alienada das suas comunidades e culturas locais, mas não foi absorvida pela sociedade e pela economia. Isso torna os jovens do sexo masculino vulneráveis a influências globais e às promessas dos seus pares, às vezes relacionados com redes de pensamento religioso radical e de criminalidade. O ensaio analisa também a medida em que a parte nordeste de Moçambique, com os seus enormes investimentos numa indústria de Gás Natural Liquefeito (GNL), é vulnerável à influência do islamismo militante. O estudo termina com sugestões para enfrentar os conflitos locais, que surgem numa altura em que a «guerra» de longa data entre o Governo da Frelimo e a Renamo está a ser negociada visando um acordo político.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Walking the talk?: A critical perspective on sustainable peace and reconciliation in Mozambique - Weimer, Bernhard (Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, 2020)
The August 2019 Maputo Accord on Peace and Reconciliation appears not to be standing on entirely solid ground. Not only has the decentralization agreement suffered from last minute ‘adulteration’, but also the DDR process has been lacking speed and rigour. The circumstances and outcomes of the October 2019 elections have cast doubt on the extent to which Renamo will abide to the August 2019 agreement. The party appears to be split on the matter of the – officially disowned armed Junta Militar maintaining low-intensity, nevertheless deadly, attacks on civilian traffic in central Mozambique. Thus it remains doubtful at the beginning of 2020 to what extent the ambitious DDR process, the key Pillar/Provision of the most recent peace agreement, may be implemented and by when. Further, the institutional setup of the Peace Secretariat and the donor-financed MDTF for DDR process leave doubts about national ownership of and responsibility for the implementation of the Peace Agreement, which uses reconciliation as a token, but avoids getting to its substance. Apart from these factors, the summary amnesty legislation benefitting both former warring parties prevents the possibility of publicly discussing justice and pursuing war crimes. With Frelimo’s impressive, albeit amply contested, win of the 2019 elections at the national level and provincial tier of government, the paradigm of ‘winner takes all’ may come back into political reality, which in the past had triggered armed conflict and prompted political negotiations on some degree of power sharing through decentralization arrangements. In some senior political circles, this paradigm is now paraphrased as the introduction of a benevolent authoritarian African regime, at the cost of democratic checks and balances and a strong civil society. Under these circumstances, reconciliation initiatives as sketched above , primarily promoted by civil society in the broadest sense and including FBOs, would seem a viable strategy to breathe new life into the August 2019 agreement and opening space for the youth to actively engage the political parties which, up to today, they had talked peace but remained prepared for war. Only Chissano, in the aftermath of the Rome General Peace Accord, attempted to ‘walk the reconciliation talk’. The present constellation and the terrible consequences for lives and livelihoods in Cabo Delgado would also represent a strategic opportunity to become actively involved in peace consolidation, from which the Mozambican CSOs have been kept at a distance, leaving peace-making to political leaders only. A Malawian proverb suggests that he who thinks he is leading but has no followers is only taking a walk.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict - civil war / conflito - guerra civil; conflict / conflito

Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude